Adsorption Properties of Activated Carbons Prepared from Olive Stones by Chemical and Physical Activation - M.N. Alaya; M.A. Hourieh; A.M. Youssef; F. El-Sejariah (Adsorption Science & Technology)
Activated carbons were prepared from olive stones either by the addition of zinc chloride (25–50 wt%) or by gasifying non-activated carbon with steam to burn-offs between 25% and 49%. The adsorption of nitrogen at 77 K was investigated and the adsorption data interpreted by the application of the Langmuir equation, the BET equation and the α S -method. The adsorption of carbon dioxide at 273 K was also followed and the data analyzed using the DR and DA equations. The adsorption of iodine from aqueous potassium iodide solution, and of Methylene Blue and p -nitrophenol from aqueous solutions at 298 K was also determined. Activation with zinc chloride produced physical and chemical changes which modified the thermal degradation process. Carbonization with zinc chloride restricted the formation of tars with the subsequent formation of solid carbon, the amount of zinc chloride incorporated in the precursor governing the porosity of the resulting carbon. The atmosphere under which activation of samples containing zinc chloride was undertaken was another factor in determining the texture of the carbon. Activation with steam to low burn-offs created new micropores by burning off the more reactive carbon atoms, but at high burn-offs erosion of the pore walls occurred leading to pore widening. Adsorption from solution was determined by the solubility of the solute in the solvent and by competition for this solute between the solvent and the adsorbent. The pore size of the carbon adsorbent and the molecular size of the adsorbate molecule were prominent factors in determining the extent of adsorption from solution.